Genomic characterisation of bovine papillomavirus types 1 and 2 identified in equine sarcoids in Japan. (8th January 2021) - Yamashita‐Kawanishi, Nanako; Chambers, James K.; Uchida, Kazuyuki; Tobari, Yumiko; Yoshimura, Hisashi; Yamamoto, Masami; Yumoto, Norio; Aoki, Hiroshi; Sugiura, Katsuaki; Higuchi, Tohru; Saito, Shigeaki; Haga, Takeshi
Abstract: Background: Bovine papillomavirus types 1 and 2 (BPV1/2) infection in horses has been associated with the development of equine sarcoids. Previous findings revealed the presence of sarcoid‐associated BPV sequence variants that have been proposed as a key factor of cross‐species infection in horses. To verify this hypothesis, sarcoid‐associated BPV variants should be identified regardless of geographic location. Objectives: Sequence analyses of BPV1/2 derived from both horses and cattle were conducted to clarify the sarcoid‐associated sequence variants. The aim of this study was to clarify the correlation between BPV phylogeny and the geographic origin/host species. Study design: Cross‐sectional study. Methods: Conventional PCR to detect BPV1/2 was performed with genomic DNA extracted from equine sarcoid (n = 10) and bovine papilloma (n = 10) samples collected in Japan. Direct sequencing results were compared between equine and bovine (equine/bovine)‐derived BPV to identify sarcoid‐associated variants of two early regions (E2, E5), one late region (L1) and the long control region (LCR). Phylogenetic and phylogeny‐trait correlation were analysed using Bayesian Markov chain Monte Carlo (MCMC) method and Bayesian tip‐association significance testing (BaTS). Results: Seven BPV1 and three BPV2 were identified from equine sarcoids using PCR and direct sequencing. Sequence analysis of equine/bovine‐derived samples showed no sarcoid‐associated variants in four regions (E2, E5, L1 and LCR) of either BPV1 or BPV2. The phylogenetic tree of BPV1 E2, L1 and LCR tended to cluster within its geographic origins. BaTS analysis demonstrated that BPV1 sequence variability may be due to the geographic origin rather than host species difference. Main limitations: There was a limitation in sample numbers. Conclusions: This study supports the geographic‐specific hypothesis of sequence variability, suggesting that BPV1 is shared between local equids and bovids. However, more extensively collected sequences worldwide and functional evaluations are needed to verify the geographic‐specific sequence variability of BPV1/2 between equine‐ and bovine‐derived sequence.